Analysis of Listening Skills in The HSK 4 Test Simulation Among Mandarin Department Students at University in Makassar - Azizah, Mirah; Marsuki, Ria Riski; Riski, Hasria (Universitas Negeri Semarang, 2025)
This research, titled Analysis of Listening Skills in the HSK 4 Test Simulation Among Mandarin Language Department Students at a University in Makassar, identifies factors or obstacles that may affect the Mandarin language learning of fourth-semester students, particularly in relation to errors made during the HSK 4 listening simulation test, based on results collected through Google Forms and Zoom. Due to a lack of understanding of the question context and audio conversations, many participants made mistakes in answering the questions. This study aims to analyze the listening skills of fourth-semester students in the Mandarin language education program at a university in Makassar in completing the HSK 4 listening simulation test.